The Reinforcement of Foreigner Satisfaction Concept in Immigration Service in Indonesia - Dasman Lanin; Nailuredha Hermanto (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2017)
This research discuss about the Reinforcement of Foreigner Satisfaction Concept in immigration service in Indonesia. Policy implementation and law enforcement will be much easier if the government can gain trust from its citizen (Zhao and Hu, 2015), even in a more extreme case, the low trust in government can push reformation (Salim et al., 2017). Immigration service is not only provided for Indonesian but also for foreigners that enter Indonesia territory. Few immigra- tion services provided for foreigners are visa and stay permit extension, stay per- mit shifting, multiple exit re-entry permit, and dual citizenship for children under 18 years old. This research aims to prove the influence of equity and disconfirmation satisfaction on CSI as intervening variables in order to re-formu- late the more representative CSI concept. This was a quantitative research that was conducted in Padang Immigration Office. The sample was counted by using Slovin formula. Based on all findings and discussion above, we concluded that the rein- forcement of foreigner satisfaction concept can be done by adding equity satis- faction and disconfirmation satisfaction into existing CSI model because both of them can increase the influence of service quality on SCI. Furthermore, the proposed hypothetic model was proved and it can be accounted for academically. The model can be used as the conceptual corner- stone by other researchers to do other studies related to service quality and CSI.